Delayed Diagnosis of Congenital Hypoparathyroidism in a Kindred of Three Patients With Autosomal Dominant Deafness - Dandurand, Karel (J Endocr Soc, 2021)
Background: Congenital hypoparathyroidism can be related to autosomal dominant mutations or deletions in GATA-binding protein 3 gene on chromosome 10(1,2). Affected patients present with a triad of hypoparathyroidism, renal dysplasia and neurosensorial deafness. We hereby present the case of a patient with the rare Barakat syndrome, also known as HDR syndrome. Clinical Case: A 11-year-old girl, diagnosed with deafness at birth, was brought to medical attention because of menorrhagia requiring blood transfusions two months after menarche. A pelvic ultrasound demonstrated a septate uterus as well as right multicystic dysplastic kidney with solitary left kidney and ovary. As her maternal grandmother, mother and older sister suffered from congenital deafness and her mother also had a kidney cyst, the patient was referred to genetics to identify a unifying cause of the autosomal dominant pattern of deafness and urogenital anomalies. Chromosome microarray analysis revealed a copy number change on chromosome 10p14 of 1925 kb predicted to result in the deletion of a single protein coding gene, GATA3. Embryonically, GATA3 is involved in the development of the inner ear, kidneys and parathyroid glands. The patient was lost to follow up so that a serum calcium was drawn three years later, revealing low ionized calcium of 1.06 mmol/L (N 1.16–1.29), low corrected total calcium of 2.11 mmol/L (N 2.30–2.62) along with PTH of 1.1 pmol/L (N 2.0–9.4), PO4 of 1.73 mmol/L (N 1.03–1.78) and creatinine of 64 umol/L (N 50–71). She was started on calcium carbonate 1000 mg TID and calcitriol 0.5 mcg BID and genetic analysis of the mother and sister revealed the same mutation compatible with Barakat syndrome. Compliance has been difficult, and when the patient transitioned to adult endocrinology three years later, she was on alfacalcidiol 2 mcg daily along with calcium carbonate 1500 mg daily and her labs were still suboptimal with a total corrected calcium of 1.82 mmol/L (N 2.22–2.54) and ionized calcium 0.98 mmol/L (N 1.16–1.29). Renal function determines the prognosis, and reassuringly her creatinine remains normal. Upon further questioning of the mother, she recalls that the patient had to be intubated for respiratory failure as a newborn, she had delayed milestones and also had seizure like activity during her infancy and early childhood. She had brought these symptoms to her family physician’s attention however no further investigations were completed and serum calcium was not checked. Conclusion: Early recognition of hypocalcemia symptoms is critical in identifying patients with congenital hypoparathyroidism, even more so when associated with other features that are part of complex familial syndrome such as Barakat syndrome. 1. Barakat, AJ. Barakat syndrome revisited. Am J of Med Genet A. 2018, Jun; 176(6):1341–13482. Barakat, AY. Familial nephrosis, nerve deafness and hypoparathyroidism. J Pediatri. 1977;9(1):61